TCI remifentanil for fetal immobiliztion and analgesia during Ex-Utero Intrapartum (EXIT) Surgical Airway for fetal with congenital high airway obstruction syndrome (CHAOS). - Abdul Karim, Othman; Mohd Habibullah, Zakaria; Noraslawati, Razak; Ruwaida, Isa (2018)
In performing a delicate fetal airway surgery, the fetal must achieve adequate analgesia and more importantly immobilization. There are several ways of achieving fetal analgesia and immobilization during EXIT procedure which include direct administration of analgesics and muscle relaxant to fetal via intravenous or intramuscular route, intra-amniotic delivery or delivery through maternal infusion. In our case, fetal analgesia and immobilization was achieved through maternal target controlled infusion of remifentanil supplemented with inhalational sevoflurane.